Analisis Yuridis terhadap Tugas dan Fungsi Debt Collector Pasca Putusan MK - I Nyoman Suwardika; I Nyoman Suandika; Ida Bagus Anggapurana Pidada (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
This research aims to determine the juridical analysis of the duties and functions of Debt Collectors after the Constitutional Court decision and to determine the impact of the post-Constitutional Court Decision on the duties and functions of Debt Collectors. The method used in this research uses the type of research used is a type of juridical analysis approach. The results of the research show that the implementation of the execution of fiduciary guarantees has undergone a change following the decision of the Constitutional Court, which is the term "executorial power" in Article 15 Paragraph (2) and the decision. court which has legal force remains contrary to the 1945 Constitution and does not have binding legal force as long as it is not interpreted as a lack of agreement in the event of a breach of contract and the debtor objects to voluntarily surrendering the object which is a fiduciary guarantee, then the implementation of legal procedures for implementing fiduciary guarantees must be carried out and likewise This is the case with the execution of court decisions that have permanent legal force. On the other hand, if a default agreement has been agreed between the debtor and creditor at the beginning of the agreement, the finance company can directly carry out its own execution without going to court. So that after the decision of the Constitutional Court, creditors can no longer carry out unilateral execution of fiduciary collateral objects, but must go through the District Court, unless there is a breach of contract agreement at the beginning of the agreement between the debtor and creditor, and the debtor voluntarily hands over the fiduciary collateral object to the creditor.